Photosynthetic, antioxidant activities, and osmoregulatory responses in winter wheat differ during the stress and recovery periods under heat, drought, and combined stress. (February 2023) - Ru, Chen; Hu, Xiaotao; Chen, Dianyu; Wang, Wene; Zhen, Jingbo
Abstract: There will be longer and more intense periods of heat and drought stress in the future for terrestrial ecosystems. Although the responses of wheat plants to heat and drought stress alone have been extensively investigated, little is known about the extent to which their recovery can be assured after stress relief. In this study, a winter wheat pot experiment was conducted to investigate the changes in photosynthetic performance, antioxidant activity, osmoregulation, and membrane lipid peroxidation under heat stress (36 °C), drought (45–55% of soil water holding capacity), and combined stress conditions. The results showed that heat and drought stress significantly reduced the photosynthetic rate and the contents of chlorophyll and carotenoid. Superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and glutathione reductase (GR) activities were greatly activated by heat and drought stress to scavenge overproduced superoxide anion (O2 - ). Plants exhibited positive osmoregulation through the synthesis of soluble protein (SP), soluble sugar (SS), and proline (Pro) to improve membrane stability. Within a range of stress, combined heat and drought stress exhibited significant interactive effects in the above mentioned indicators. After stress relief, the majority of physiological processes were reversible, as indicated by the effective recovery of pigment contents, photosynthetic rate, antioxidant enzyme activities, osmoregulatory substance contents, and O2 - production. Antioxidant enzyme activities tended to increase after recovering from 12 days of combined stress, whereas they were still not effective in mitigating oxidative damage. High levels of O2 - and malondialdehyde (MDA) and a low relative growth rate during the recovery confirmed the irreversible damage caused by combined heat and drought stress. ROC (receiver operating characteristic) analysis indicated that GR and SS could accurately detect individual heat and drought stress that wheat plants were suffering or had suffered (AUC = 0.812–0.965), while POD and Pro had greater potential for diagnosing combined heat and drought stress (AUC = 0.871–0.958). Physiological indicators of stress tolerance were closely related to the photosynthetic rate during the stress, particularly Pro and GR. Collectively, the physiological processes of plants are reversible within a certain range of stress. POD, GR, Pro, and SS play vital roles in identifying and resisting heat, drought, and combined stress, and the recovery of these indicators contributed to improving photosynthesis and thereby increasing wheat growth. Our research contributes to the understanding of the underlying physiological mechanisms of plants in response to combined heat and drought stress and after stress relief. Graphical Abstract: ga1 Highlights: The responses of physiological activity to stress and recovery periods were studied. Physiological processes of plants are reversible within a range of stresses. POD, GR, Pro, and SS play vital roles in identifying heat and drought stress. Physiological traits of stress resistance are closely related to photosynthesis.